Mechanical Integrity and Weld Characterization of FCAW and GTAW Joints on API 5L CO2 Fire Suppression Pipes - Delpero, M Arief; Hasibuan, Fardin; Putra, Wendri; Nulhakim, Buyung (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
This study investigates the mechanical and macro structural performance of welded joints produced by Flux-Cored Arc Welding (FCAW) and Gas Tungsten Arc Welding (GTAW) on API 5L Grade B low-carbon steel pipes used in marine CO2 fire suppression systems. The experimental work involved tensile, bending, hardness, and macro structural tests to evaluate the influence of each welding process on joint integrity. Both FCAW and GTAW joints exhibited high mechanical strength, with ultimate tensile strengths of 506MPa and 516MPa, respectively, exceeding the minimum requirement for API 5L Grade B steel. Fracture occurred in the base metal rather than the weld zone, confirming the superior strength and sound fusion quality of the joints. GTAW demonstrated slightly higher tensile performance and cleaner weld morphology due to the controlled heat input and stable arc achieved with 100% argon shielding, whereas FCAW produced marginally higher hardness in the heat-affected zone due to CO?-induced cooling effects. Macro structural analysis revealed complete penetration and the absence of porosity, slag inclusions, or cracks in both processes. The results comply with AWS D1.1 and ASME Section IX standards, confirming that both welding methods or their hybrid application are suitable for producing safe, reliable, and regulation-compliant marine fire suppression pipelines.